Past and future dynamics of the Brunt Ice Shelf from seabed bathymetry and ice shelf geometry - Hodgson, Dominic A.; Jordan, Tom A.; de Rydt, Jan; Fretwell, Peter T.; Seddon, Samuel A.; Becker, David; Hogan, Kelly A.; Smith, Andrew M.; Vaughan, David G. (Copernicus, 2019)
The recent rapid growth of rifts in the Brunt Ice Shelf appears to signal the onset of its largest calving event since records began in 1915. The aim of this study is to determine whether this calving event will lead to a new steady state where the Brunt Ice Shelf remains in contact with the bed, or an unpinning from the bed, which could pre-dispose it to accelerated flow or possible break-up. We use a range of geophysical data to reconstruct the seafloor bathymetry and ice shelf geometry, to examine past ice sheet configurations in the Brunt Basin, and to define the present-day geometry of the contact between the Brunt Ice Shelf and the bed. Results show that during past ice advances grounded ice streams converged in the Brunt Basin from the south and east. The ice then retreated pausing on at least three former grounding lines marked by topographic highs, and transverse ridges on the flanks of the basin. These have subsequently formed pinning points for advancing ice shelves. The ice shelf geometry and bathymetry measurements show that the base of the Brunt Ice Shelf now only makes contact with one of these topographic highs. This contact is limited to an area of less than 1.3 to 3km2 and results in a compressive regime that helps to maintain the ice shelf. The maximum overlap between ice shelf thickness and the bathymetry is 2–25m, and is contingent on the presence of incorporated iceberg keels, which protrude beneath the base of the ice shelf. The future of the ice shelf is dependent on whether the expected calving event causes full or partial loss of contact with the bed, and whether the subsequent response causes re-grounding within a predictable period, or a loss of structural integrity resulting from properties inherited at the grounding line.